Historisasi Pemuda Gua Kahfi dalam Tinjauan Islam - Muhammad, Muhammad; Sahrin, Abu; Putri, Kamelia Ji (ANWARUL, 2023)
Story is one of the five main content of the Koran. Even two-thirds of the content of the Al-Quran is in the form of stories. This is because the stories in the Koran are unique and special compared to other stories. In this study the author will reveal one of the stories in the Koran, namely the story of Ashabul Kahf which is found in surah Al-Kahf verses 9-26. Ashabul kahfi was a young man who was determined at that time, they were willing to leave their village for the sake of their faith which had been firmly entrenched in their souls. They asked Allah for help and for mercy. Allah also granted their request by showing them to a cave that was on the top of the mountain as a place to hide, in the cave they felt the grace of Allah that had been poured out on them by putting them to sleep for 309 years, then waking them up in a state of body that had not changed in the slightest This research uses a type of library research (Library Research) which aims to examine and examine various documents either in the form of books or writings related to the discussion of the Historization of the Kahf Cave in an Islamic Review. This study uses a comparative method, which aims to provide an overview of the phenomenon under study by comparing facts from two different objects or samples